INVESTIGATION OF ACADEMIC PROCRASTINATION: A CASE STUDY IN ISLAM-AFFILIATED UNIVERSITY - Pradana, Silmi Asyan; Yuniarti, Yuniarti (Universitas Muhammadiyah Lampung, 2025)
Until recently, studies on academic procrastination involving students with diverse secondary school backgrounds have received limited attention, although an extensive body of research has been conducted on academic procrastination among university students. This study explored the current phenomenon of students‘ academic procrastination experience when completing academic writing tasks. Following qualitative analysis techniques, this phenomenon study involved nine students at a Public Islamic University in Lampung. The participants were selected through a purposive sampling technique. Research data were obtained from survey result and in-depth interviews with the participants. The findings of the study show that the majority of academic proctrastinators, categorized as passive procrastinators, come from high school and vocational school backgrounds. Meanwhile, the majority of active procrastinators are from Islamic boarding schools. This difference is influenced by personality traits, with passive procrastinatorsexhibiting a stronger tendency toward extraversion, while active procrastinatorsare more dominant in the agreeableness trait. Furthermore, the Avoidance-Oriented Coping Mechanisms emerges as the most often used by students to overcome academic procrastination. The findings of this study will provide valuable insights for students to avoid academic procrastination, will help lecturers in designing suitable tasks, and will contribute to enriching discussion about academic procrastination.